Comparison of gaseous and particulate emissions from a pilot-scale combustor using three varieties of coal. (1st March 2018) - Yelverton, Tiffany L.B.; Brashear, Angelina T.; Nash, David G.; Brown, James E.; Singer, Carl F.; Kariher, Peter H.; Ryan, Jeffrey V.
Abstract: Gaseous and particulate emissions generated from the combustion of coal have been associated with adverse effects on human health and the environment, and have therefore been the subject of regulation by federal and state government agencies. Detailed emission characterizations are needed to better understand the impacts of pre- and post-combustion controls on a variety of coals found in the United States (U.S.). While the U.S. Environmental Protection Agency (EPA) requires industry reporting of emissions for criteria and several hazardous air pollutants (HAPs), many of the methods for monitoring and measuring these gaseous and particulate emissions rely on time-integrated sampling techniques. Though these emissions reports provide an overall representation of day-to-day operations, they represent well-controlled operations and do not encompass real combustion events that occur sporadically. The current study not only characterizes emissions from three coals (bituminous, sub-bituminous, and lignite), but also investigates the use of instrumentation for improved measurement and monitoring techniques that provide real-time, continuous emissions data. Testing was completed using the U.S. EPA's Multi-Pollutant Control Research Facility, a pilot-scale coal-fired combustor using industry-standard emission control technologies, in Research Triangle Park, North Carolina. Emissions were calculated based on measurements from the flue gas (pre- and post-electrostatic precipitator), to characterize gaseous species (CO, CO2, O2, NOX, SO2, other acid gases, and several organic HAPs) as well as fine and ultrafine particulate (mass, size distribution, number count, elemental carbon, organic carbon, and black carbon). Comparisons of traditional EPA methods to those made via Fourier Transfer Infrared (FTIR) Spectroscopy for CO, NOX, and SO2 are also reported.